A Kalman Filter Approach to PCB Drill Path Optimization Problem - Abdul Aziz, Nor Hidayati; Zuwairie, Ibrahim; Ab. Aziz, Nor Azlina; Saifudin, Razali; Abas, Khairul Hamimah; Mohamad, Mohd Saberi (Institute of Electrical and Electronics Engineers, 2017)
Drill path optimization problem is an important problem in holes drilling with computer numerically controlled (CNC) machine. Due to the exponential increase in the number of possible solutions when the number of holes to be drilled increase, the metaheuristic optimization algorithm seems to be a good choice in solving this type of optimization problem. This paper presents a Kalman Filter approach in solving printed circuit board (PCB) routing problem by using the Simulated Kalman Filter (SKF) algorithm. The experimental results are compared with those obtained by swarm intelligence approach, which are the Particle Swarm Optimization (PSO) variants, Ant Colony System (ACS) and Cuckoo Search (CS). The implementation proves to be effortless with good global convergence capability.